Risk factors of cervical insufficiency in women with PCOS undergoing IVF-ET treatment: a case-control study - Zhao, Xueqing; Ye, Shenglong; Yan, Xin; Li, Rong; Wang, Yongqing (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to investigate the risk factors associated with cervical insufficiency (CI) in women with polycystic ovarian syndrome (PCOS) who have undergone in vitro fertilization and embryo transfer (IVF-ET) treatment.MethodsThis study included 746 women diagnosed with PCOS. These women successfully achieved pregnancy through IVF-ET between 2016 and 2023 and subsequently delivered at Peking University Third Hospital. Women were categorized into a study group and a control group based on the presence of CI. Additionally, stratified analyses were performed within each group according to whether fresh or frozen embryos were used for transfer, to investigate the clinical characteristics and risk factors associated with CI.ResultsIn women with PCOS undergoing IVF-ET, BMI (OR=1.195, 95% CI: 1.043-1.290, P<0.001), AMH (OR=1.158, 95% CI: 1.092-1.227, P<0.001), frequency of hysteroscopy operations (OR=1.587, 95% CI: 1.202-2.094, P=0.001), prior gravidity (OR=1.956, 95% CI: 1.459-2.621, P<0.001), and occurrence of twin pregnancies (OR=3.028, 95% CI: 1.563-5.865, P=0.001) were found to be positively associated with the incidence of CI. The cut-off value of BMI and AMH were respectively 22.25kg/m2 and 9.965ng/ml. Different IVF-ET protocols and hysteroscopic operation within 6 months before pregnancy is not a risk factor for CI. Among women with PCOS undergoing fresh embryo transfer, elevated androstenedione levels (OR=3.250, 95% CI: 1.129-9.359, P=0.029) were identified as a risk factor for CI. In contrast, for women with PCOS undergoing frozen embryo transfer, multiple factors including BMI (OR=1.254, 95% CI: 1.134-1.388, P<0.001), AMH levels (OR=1.232, 95% CI: 1.144-1.327, P<0.001), frequency of hysteroscopy procedures (OR=1.603, 95% CI: 1.155-2.224, P=0.005) and prior gravidity (OR=2.423, 95% CI: 1.674-3.508, P<0.001), were associated with an increased risk of CI.ConclusionThe study analysed risk factors for cervical insufficiency in women with PCOS who underwent IVF-ET treatment, such as BMI, AMH, frequency of hysteroscopy operations, prior gravidity, twin pregnancy. Providing a basis for the identification and prediction of people at high risk of cervical insufficiency.